{(3x,+,y,=,9),(2x,-,y,=,1):} Add equation (1) and (2): 5x = 10 x = 2 Substitute x = 2 into equation (1) and solve for y: 3 xx 2 + y = 9 6 + y = 9 y = 9 – 6 y = 3 Thus, the solution is (2,3)

Question

asked 2021-02-19

Solve the system of equations.
{(x,+,4y,=,-2),(-2x,+12y,=,9):}

asked 2021-02-10

Solve the system: {(-3x,+,y,=,2),(9x,-,3y,=,-6):}

asked 2021-02-10

Solve the system: {(-2x,+,y,=,5),(-6x,+,3y,=,21):}

asked 2021-01-19

Please, solve the system of equations:
{(5x,+,y,=,14),(2x,+,y,=,5):}

asked 2021-01-31

Solve
{(x,+,2y,=,9),(y,=,-2x):}

asked 2021-02-20

What is the solution of the system of equations?

y = 2x - 3

5x + y = 11

A (2, 1)

B (1, 2)

C (3, -4)

D (1, -1)

y = 2x - 3

5x + y = 11

A (2, 1)

B (1, 2)

C (3, -4)

D (1, -1)

asked 2020-12-22

Solve
{(2x,+,3y,=,-1),(6x,+,3y,=,-9):}

asked 2020-11-09

x-y+2x=3

2x+z=1

3x+2y+z=4

2x+z=1

3x+2y+z=4

asked 2020-10-25

What are the solutions to the following system of equations?

\(y = x^{2} + 3x − 7\)

\(3x − y = −2\)

\(y = x^{2} + 3x − 7\)

\(3x − y = −2\)

asked 2021-02-09

Solve by substitution.

y = -2x + 1

y = -6x - 11

y = -2x + 1

y = -6x - 11